2022
DOI: 10.1002/ijfe.2717
|View full text |Cite
|
Sign up to set email alerts
|

Volatility spillovers during normal and high volatility states and their driving factors: A cross‐country and cross‐asset analysis

Abstract: Understanding the transmission of volatility across markets is essential for managing risk and financial stability, especially under crisis periods during which an extreme event occurring in one market is easily transmitted to another market. To gain such an understanding and enrich the related literature, we examine in this article the system of volatility spillovers across various equity markets and asset classes using a quantile‐based approach, allowing us to capture spillovers under normal and high volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Besides, the plots of timevarying total spillover at both the conditional mean and median suggest that over the sample period, the level of total spillover appear to have intensified during the first wave of the COVID-19 pandemic in the first two quarters of 2020, especially when total spillover is measured at the conditional mean using the standard Diebold and Yilmaz (2012) approach. Significant increase in the levels of risk spillovers among sustainable and conventional assets during the peak of the COVID-19 pandemic has been documented in previous studies (see e.g., Iqbal, Bouri et al, 2022;Iqbal, Naeem et al, 2022;Zhao et al, 2023).…”
Section: Connectedness Among Sustainable Investment and Commoditiesmentioning
confidence: 54%
See 1 more Smart Citation
“…Besides, the plots of timevarying total spillover at both the conditional mean and median suggest that over the sample period, the level of total spillover appear to have intensified during the first wave of the COVID-19 pandemic in the first two quarters of 2020, especially when total spillover is measured at the conditional mean using the standard Diebold and Yilmaz (2012) approach. Significant increase in the levels of risk spillovers among sustainable and conventional assets during the peak of the COVID-19 pandemic has been documented in previous studies (see e.g., Iqbal, Bouri et al, 2022;Iqbal, Naeem et al, 2022;Zhao et al, 2023).…”
Section: Connectedness Among Sustainable Investment and Commoditiesmentioning
confidence: 54%
“…Second, we contribute to the literature by being the first to use the QVAR method recently developed by Ando et al (2022) to analyse the interdependence between major natural resource commodities and sustainable investment. This methodology follows past leading studies on spillover in the quantiles (see e.g., Bouri & Harb, 2022;Bouri et al, 2020;Iqbal, Bouri et al, 2022;Iqbal, Naeem et al, 2022). As noted earlier, the method avails us the opportunity to characterize crossmarket linkages and the propagation of shocks across different market conditions for the studied investment indices.…”
Section: Related Literaturementioning
confidence: 99%
“…The energy-stock relationship may also differ in different market states. For instance, conditional on quantile-based method, [ 5 ] aim to describe volatility transmission among global equities, strategic commodities and the US Treasury bond market during normal and high volatility states. Note that there exist not only return and volatility spillover between energy market and stock market, higher moments namely skewness and kurtosis spillover may also contain valuable information.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the negative impact of total volatility outweighs the positive impact, indicating system-wide pessimism. Najaf et al (2022) examined the volatility spillover in various equity markets and asset classes using a quantum-based approach. They found that in a normal state of volatility, the US stock market is at the center of the volatility effect.…”
Section: Introductionmentioning
confidence: 99%